THE PERFORMANCE OF ENGINEERED WATER FLOODING TO ENHANCE HIGH VISCOUS OIL RECOVERY - Ganiyeva, Aizada; Karabayanova, Leila; Pourafshary, Peyman; Hashmet, Muhammad Rehan (Applied Sciences, 2022)
Low salinity/engineered water injection is an effective enhanced oil recovery method, con firmed by many laboratory investigations. The success of this approach depends on different criteria such as oil, formation brine, injected fluid, and rock properties. The performance of this method in heavy oil formations has not been addressed yet. In this paper, data on heavy oil displacement by low salinity water were collected from the literature and the experiments conducted by our team. In our experiments, core flooding was conducted on an extra heavy oil sample to measure the incremental oil recovery due to the injected brine dilution and ions composition. Our experimental results showed that wettability alteration occurred during the core flooding as the main proposed mechanism of low salinity water. Still, this mechanism is not strong enough to overcome capillary forces in heavy oil reservoirs. Hence, weak microscopic sweep efficiency and high mobility ratio resulted in a small change in residual oil saturation. This point was also observed in other oil displacement tests reported in the literature. By analyzing our experiments and available data, it is concluded that the application of standalone low salinity/engineered water flooding is not effective for heavy oil formations where the oil viscosity is higher than 150 cp and high oil recovery is not expected. Hence, combining this EOR method with thermal approaches is recommended to reduce the oil viscosity and control the mobility ratio and viscous to capillary forces.
Keywords: Type of access: Open Access; low salinity water; engineered water; viscosity; heavy oil; screening